Functional Architecture of the Inferior Colliculus Revealed with Voltage-Sensitive Dyes - Chandrasekaran, Lakshmi; Xiao, Ying; Sivaramakrishnan, Shobhana (Frontiers in Neural Circuits, 2013)
We used optical imaging with voltage-sensitive dyes to investigate the spatio-temporal dynamics of synaptically evoked activity in brain slices of the inferior colliculus (IC). Responses in transverse slices which preserve cross-frequency connections and in modified sagittal slices that preserve connections within frequency laminae were evoked by activating the lateral lemniscal tract. Comparing activity between small and large populations of cells revealed response areas in the central nucleus of the IC that were similar in magnitude but graded temporally. In transverse sections, these response areas are summed to generate a topographic response profile. Activity through the commissure to the contralateral IC required an excitation threshold that was reached when GABAergic inhibition was blocked. Within laminae, module interaction created temporal homeostasis. Diffuse activity evoked by a single lemniscal shock re-organized into distinct spatial and temporal compartments when stimulus trains were used, and generated a directional activity profile within the lamina. Using different stimulus patterns to activate subsets of microcircuits in the central nucleus of the IC, we found that localized responses evoked by low-frequency stimulus trains spread extensively when train frequency was increased, suggesting recruitment of silent microcircuits. Long stimulus trains activated a circuit specific to post-inhibitory rebound neurons. Rebound microcircuits were defined by a focal point of initiation that spread to an annular ring that oscillated between inhibition and excitation. We propose that much of the computing power of the IC is derived from local circuits, some of which are cell-type specific. These circuits organize activity within and across frequency laminae, and are critical in determining the stimulus-selectivity of auditory coding.